Development of Basic Chemistry II Textbook Based on Research - Elvy Rahmi Mawarnis; Sri Maiyena; Liszulfah Roza; Mohd Yusri Abd. Rahman (Postgraduate, University of Mataram, 2023)
Research based on the absence of the development of quality, innovative and integrated Research based on the absence of the development of quality, innovative and integrated Chemistry textbook with the latest research results that are used to broaden student's horizons and increase student creativity. The purpose of this research is to produce basic Chemistry II textbook based on research. This study uses a type of development research using a 4-D model which consists of 4 stages, namely, definition, design, development and dissemination. The subjects of this study were students of the Department of Chemistry Education of IAIN Batusangkar. The data were collected using a questionnaire. The results of textbook based on research validity obtained a percentage of 88.21% with highly valid category. Then, the results of the practicality test obtained a percentage of 76.31% in the practical category and the results of the effectiveness test showed a significant increase in student activities and learning outcomes. With this, it can be concluded that the basic Chemistry II textbook based on research is valid, practical and effective for use in the learning process